2016
DOI: 10.1002/cyto.a.23000
|View full text |Cite
|
Sign up to set email alerts
|

Cell size assays for mass cytometry

Abstract: Mass cytometry offers the advantage of allowing the simultaneous measurement of a greater number parameters than conventional flow cytometry. However, to date, mass cytometry has lacked a reliable alternative to the light scatter properties that are commonly used as a cell size metric in flow cytometry (forward scatter intensity—FSC). Here, we report the development of two plasma membrane staining assays to evaluate mammalian cell size in mass cytometry experiments. One is based on wheat germ agglutinin (WGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
(45 reference statements)
3
43
0
Order By: Relevance
“…See protocol [46] for conjugating antibodies with these heavy-metals. Beyond this, users can employ quantum dot labeled antibodies to gain additional channels [47], iodine for cell cycle tracking [124], RNA transcripts [131][132][133], platinum drug uptake [128,129], cell cycle status and DNA synthesis [130], cell size [125], apoptosis [48], and viability [27] Proteins, phospho-proteins, chromatin modifications [145], RNA transcripts [146], fluorescent drug uptake [147], metabolism and redox state [148,149], cell cycle status and DNA synthesis [150], cell size and granularity, apoptosis [151] and viability [152] Poly-adenylated RNA transcripts, CITE-seq probes [144] Minimum cells per sample needed at start of protocol Max is an example maximum range of the instrument scale; error is the typical error for that scale. c Includes capabilities of novel instruments such as Cytek TM Aurora (Cytek Biosciences), ZE5 TM (Bio-Rad), and FACSymphony TM (BD).…”
Section: Multiplexing Capabilitymentioning
confidence: 99%
“…See protocol [46] for conjugating antibodies with these heavy-metals. Beyond this, users can employ quantum dot labeled antibodies to gain additional channels [47], iodine for cell cycle tracking [124], RNA transcripts [131][132][133], platinum drug uptake [128,129], cell cycle status and DNA synthesis [130], cell size [125], apoptosis [48], and viability [27] Proteins, phospho-proteins, chromatin modifications [145], RNA transcripts [146], fluorescent drug uptake [147], metabolism and redox state [148,149], cell cycle status and DNA synthesis [150], cell size and granularity, apoptosis [151] and viability [152] Poly-adenylated RNA transcripts, CITE-seq probes [144] Minimum cells per sample needed at start of protocol Max is an example maximum range of the instrument scale; error is the typical error for that scale. c Includes capabilities of novel instruments such as Cytek TM Aurora (Cytek Biosciences), ZE5 TM (Bio-Rad), and FACSymphony TM (BD).…”
Section: Multiplexing Capabilitymentioning
confidence: 99%
“…In a recent publication, Stern et al showed that the lipid stain osmium tetroxide (which is detectable on a mass cytometer) correlates with forward light scatter and can be used as a proxy for cell size. There is of course no guarantee that the amount of lipids would always be proportionate to cell volume and, indeed, eosinophils exhibited disproportionately strong staining compared to other blood cell types.…”
Section: Indirect Methods: Light Scattering and Cell Stainingmentioning
confidence: 99%
“…Accurately measuring single-cell size remains a challenge for mammalian cells due to their irregular shape. Existing techniques require specialized hardware, fluorescent labeling 10,11 and/or cell suspension [12][13][14][15][16] . Fluorescent labeling or over-expression of a target marker can alter cell function.…”
mentioning
confidence: 99%